Effect of temperature on structural properties of Aloe vera (Aloe barbadensis Miller) gel and Weibull distribution for modelling drying process - Miranda, Margarita (2010)
Aloe vera (Aloe barbadensis Miller) gel was dried at five inlet temperatures 50, 60, 70, 80 and 90 ◦C, in a convective dryer with a constant air flow of 2.0±0.2 m/s. Rehydration ratio, water holding capacity, texture, microstructure and total polysaccharide content were evaluated. Drying kinetics was estimated using the Weibull distribution (r2 > 0.97 and Chi-square < 0.0009). Values of scale and shape parameters ranged from 90.94 to 341.06 (min) and 1.43 to 1.49, respectively. Furthermore, the influence of temperature on the model parameters as well as on the quality attributes was analysed using a least significant difference test (p-value < 0.05). These effects were more evident for the long drying period (e.g. 810 min at 50 ◦C). However, minor alterations in the structural properties and total polysaccharide content were produced at drying temperatures of 60–70 ◦C, resulting in a high quality gel.